2022
DOI: 10.1029/2021gl097526
|View full text |Cite
|
Sign up to set email alerts
|

Standing Alfvén Waves Within Equatorial Plasma Bubbles

Abstract: Plasma depletions in the disturbed equatorial ionosphere are known to be associated with magnetic fluctuations and Alfvén waves. Here, using data from the Swarm B satellite's vector field magnetometer and electric fields instrument at an altitude of ∼500 km, we present evidence of standing Alfvén modes trapped within strong density depletions. Fourier transforms of electric (δE) and magnetic (δB) perturbations reveal harmonic structure with anticorrelated peaks and relative phase shifts approaching ±90°, in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Dao et al (2013) developed a 3-D simulation of the electric and magnetic fields resulting from current divergence, current flows, and Alfvén waves associated with plasma bubbles. Evidence consistent with Alfvén waves inside plasma bubbles has been reported in in-situ studies (Ghadjari et al, 2022;Lühr et al, 2014;Pottelette et al, 2007;Rodríguez-Zuluaga & Stolle, 2019). Simões et al (2012) detected signatures of the ionospheric Alfvén resonator (IAR) in the equatorial ionosphere in the frequency range of 0-40 Hz using electric field measurements on the Communications/Navigation Outage Forecasting System (C/NOFS) satellite.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Dao et al (2013) developed a 3-D simulation of the electric and magnetic fields resulting from current divergence, current flows, and Alfvén waves associated with plasma bubbles. Evidence consistent with Alfvén waves inside plasma bubbles has been reported in in-situ studies (Ghadjari et al, 2022;Lühr et al, 2014;Pottelette et al, 2007;Rodríguez-Zuluaga & Stolle, 2019). Simões et al (2012) detected signatures of the ionospheric Alfvén resonator (IAR) in the equatorial ionosphere in the frequency range of 0-40 Hz using electric field measurements on the Communications/Navigation Outage Forecasting System (C/NOFS) satellite.…”
supporting
confidence: 54%
“…Heilig and Sutcliffe (2016) reported compressional Pc3 (6.7–100 mHz) waves originating upstream in the solar wind and propagating to the equatorial ionosphere as seen in Swarm data. Other studies (Ghadjari et al., 2022; Kim et al., 2020a, 2020b) have reported that equatorial plasma bubbles can trap Pc1 waves. Vorontsova et al.…”
Section: Introductionmentioning
confidence: 89%
“…In a recent paper, Ghadjari et al (2022) deduced for two plasma bubble events a length of 100-200 km from standing Alfvé n wavelength estimates inside the depleted volume. These numbers are much lower than our results.…”
Section: Discussionmentioning
confidence: 99%
“…Yokoyama et al (2014) derived from their high-resolution 3D bubble model the complex evolution of depleted regions showing bifurcations and pinching in the equatorial region. A recent study by Ghadjari et al (2022) provided the evidence for standing Alfvé n waves trapped within the EPBs, and the authors further estimated the fieldaligned length of the EPBs within the range of 110-200 km, which is much smaller than the field line length of a fluxtube reaching from the E region into F region. However, these authors analyzed only two quite special examples of EPBs.…”
Section: Introductionmentioning
confidence: 98%
“…Vertical dashed lines with different colors mark important changes in the flight formation. During the first two months of the mission (November 2013 ∼ January 2014; to the left of the red dashed line in Figure 2), the Swarm satellites were under a string‐of‐pearls configuration (e.g., Ghadjari et al., 2022). The magnitudes of TDOA (Figure 2a) and Δ GLON (Figure 2b) increased together with time, as already mentioned in Section 1.…”
Section: Instruments and Data Processing Methodsmentioning
confidence: 99%